The circle - Panahi, Jafar; Partovi, Kambozia (Fox Lorber Films, 2001)
This film offers insights into the lives of women in Iran. As the narrative dynamically shifts from woman to woman, their stories culminate with tremendous potency, transforming a shared sense of despair and injustice into hope.